2012
DOI: 10.1590/s1516-35982012000800010
|View full text |Cite
|
Sign up to set email alerts
|

Sources of organic trace minerals in diets for weaned piglets

Abstract: -One hundred and twenty six piglets from a commercial genetic strain weaned at 21 days of age (6.11±0.42 kg) were used to evaluate the effects of supplementation levels of organic sources of trace minerals in the diets of weaned piglets on performance, occurrence of diarrhea, excretion of copper and zinc in the feces, and hematological parameters. A completely randomized block design was adopted, composed of six treatments (diets containing 100% of inorganic trace minerals premix at 3.00 kg/T; diets containing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 3 publications
(6 reference statements)
0
4
2
Order By: Relevance
“…Differently from our findings, Mello et al evaluating the supplementation of piglet nursery diets using a chelated trace source, found an optimal level by replacing the saline source for the organic source at approximately 25% substitution [13]. Working with Ca proteinate supplementation for turkey hens, Grimes et al reported greater hatchability values in the incubated eggs [15].…”
Section: Discussioncontrasting
confidence: 92%
See 1 more Smart Citation
“…Differently from our findings, Mello et al evaluating the supplementation of piglet nursery diets using a chelated trace source, found an optimal level by replacing the saline source for the organic source at approximately 25% substitution [13]. Working with Ca proteinate supplementation for turkey hens, Grimes et al reported greater hatchability values in the incubated eggs [15].…”
Section: Discussioncontrasting
confidence: 92%
“…The effects of high temperatures on the performance of lactating sows is well established [13]. In tropical climate conditions, the temperature observed in different seasons is always higher than the upper limit of the sows' thermoneutral zone (i.e., 22°C; Quiniou and Noblet, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, it is observed that the effect of non supplementation becomes more pronounced from the second week post-weaning, worsening the performance of piglets. The absence of trace mineral supplementation for piglets from 53 days old was observed by Mello et al (2012), suggesting that the body reserves would be insufficient to meet the requirement for trace minerals in piglets from this age.…”
Section: Performance and Diarrhea Occurrencementioning
confidence: 99%
“…Mello et al (2012), comparing levels of supplementation of trace minerals in organic form, noted that the level of 25% of what is required promoted performance similar to animals fed diet containing the total requirement. Likewise, the possibility of reducing up to 30% of trace minerals requirement in diets for pigs was demonstrated by Burkett et al (2005), when supplemented in organic form.…”
Section: Performance and Diarrhea Occurrencementioning
confidence: 99%
“…The following supporting information can be downloaded at: , Table S1: Database used in meta-analysis approach of copper fonts and levels supplemented in nursery piglet’s diets [ 10 , 11 , 29 , 30 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 ,…”
mentioning
confidence: 99%